One nation on the air: the centripetalism of radio drama and American civil religion, 1929-1962 - Wedel, Kip A. (Kansas State University, 2011)
During the 1950s, a decade scholars call the high point of American civil religion, journalist and historian William Lee Miller complained that the “popular religious revival is closely tied to a popular patriotism, of which it is the uncritical ally: religion and Americanism, god and country, Cross and flag.” If it bothered Miller that Americans too often “slipped unnoticing from one to the other,” he suspected that at least part of the problem had to do with mass media. “It is ‘salable’ religion,” he quipped, “quite clearly and often quite candidly cut to fit the requirements of Hooper ratings, box offices, and newsstand sales.” This study examines the relationship between American civil religion and radio drama in the 1950s as well as the two decades that shaped the 1950s, the 1930s and 1940s. It argues that by adapting an earlier tradition of civil religion to the twentieth century’s popular, mass-mediated culture, radio drama reinforced the centripetalism of American public life in those decades. Radio was the right medium at the right time for a nation new to global leadership and eager to rebuild its economy. As a national medium, radio enabled civil religion to continue its role in helping to forge a national identity, and as an emotionally intense medium — or what media theorist Marshall McLuhan called a “hot” medium — radio connected individual Americans to an ethereal, imagined “community of the air.” This study sheds light on constructions of the mid-twentieth century as an era of consensus in the United States by examining how centripetalism was constructed not simply by specific actors, such as the federal government and corporate broadcasting networks, but also by the specific properties of the dominant national medium, radio, and by radio’s ability to unite Americans around deep-seated civil religious understandings of their nation. It contributes to the scholarly conversation about civil religion by locating it not only in official pronouncements and public ceremonies, but also in commercial, mass-mediated cultural products, something most Americans consumed daily.
Keywords: Radio; Civil religion; American History (0337); Mass Communications (0708); Religious History (0320)